Dopaminergic Meso-Cortical Projections to M1: Role in Motor Learning and Motor Cortex Plasticity - Hosp, Jonas A.; Luft, Andreas R. (Frontiers in Neurology, 2013)
Although the architecture of a dopaminergic (DA) system within the primary motor cortex (M1) was well characterized anatomically, its functional significance remained obscure for a long time. Recent studies in rats revealed that the integrity of DA fibers in M1 is a prerequisite for successful acquisition of motor skills. This essential contribution of DA for motor learning is plausible as it modulates M1 circuitry at multiple levels thereby promoting plastic changes that are required for information storage: at the network level, DA increases cortical excitability and enhances the stability of motor maps. At the cellular level, DA induces the expression of learning-related genes via the transcription factor c-Fos. At the level of synapses, DA is required for the formation of long-term potentiation, a mechanism that likely is a fingerprint of a motor memory trace within M1. DA fibers innervating M1 originate within the midbrain, precisely the ventral tegmental area (VTA) and the medial portion of substantia nigra (SN). Thus, they could be part of the meso-cortico-limbic pathway – a network that provides information about saliency and motivational value of an external stimulus and is commonly referred as “reward system.” However, the behavioral triggers of the release of dopamine in M1 are not yet identified. As alterations in DA transmission within M1 occur under various pathological conditions such as Parkinson disease or ischemic and traumatic brain injury, a deeper understanding of the interaction of VTA/SN and M1 may reveal a deeper insight into a large spectrum of neurological disorders.